Normalized Cumulative Ranks for Maize Breeding and Varietal Recommender System (Global Journal of Science Frontier Research, 2024)
Nine varieties of maize Zea mays L namely H4226 RAJAJI TMMH826 TATA 849 KAVERI 25K-60 RMH 1818 KANAK BISCO-940 and RASI 4640 were evaluated on thirteen parameters in a randomized block design with three replications The objectives of the experiment were to select suitable plant types based on considering all the thirteen parameters suggesting scope for further improvement and recommending suitable maize ideotypes for cultivation by farmers of this region Normalized cumulative ranks analysis found BISCO-940 KAVERI 25K-60 H4226 TATA 849 and TMMH826 to be top five varieties that could be recommended to farmers for cultivation on the criteria of less number of leaves per plant small and narrow leaves with high venation early tasseling and silking dwarf plant types with lower cob placement long cobs with less number of bracts for ease of peeling off the cobs and thick cobs with more kernels and kernel rows There is scope for further improvement in the top performer variety BISCO-940 in characters like cob length early tasseling and silking All these three characters could be improved by crossing BISCO-940 with a single variety TMMH826 If this cross proves to be a heterotic combination then a hybrid maize variety could be thought or synthetics and composites could be developed from top five best performers Thus normalized cumulative ranks analysis is an excellent versatile tool for plant breeding and varietal recommender system
Keywords: composites; hybrid maize; normalized cumulative ranks; synthetics and varietal recommender system